Pendekatan Mujāhadah terhadap Pengurusan Keluarga Miskin Luar Bandar: Satu Sorotan Awal: (Mujāhadah Approach to the Management of Rural Poor Families: A Preliminary Highlights) - Binti En Abdul Rahim, Nur Izyanti Afiqah; Pa’ad, Nur Shahidah; Sa’ari, Che Zarrina (Online Journal of Research in Islamic Studies, 2025)
Poverty is a global challenge that affects various aspects of life including family management. Rural poor families often face complex management issues such as limited economic resources, restricted access to quality education, inadequate housing, and heightened social pressures that further exacerbate existing stress and conflict, thereby disrupting family functioning and overall well-being. Previous studies have indicated that a spiritual approach that fosters inner strength is needed to help these families overcome such challenges, improve their quality of life, and achieve holistic well-being. Therefore, this study aims to explore the role of mujāhadah in addressing family management issues among rural poor families. A qualitative research design was employed, involving in-depth and comprehensive analysis of journal articles, books, written documents, and other academic sources to identify key issues faced by rural poor families and examine how the mujāhadah approach can offer concrete solutions. The findings reveal that mujāhadah not only strengthens spiritual resilience but also encourages physical actions such as striving for lawful sustenance, cultivating self-discipline, and fostering positive social environments. This approach has been proven to build biopsychosocial resilience and instill consistent self-awareness, thereby enabling poor families to break the cycle of poverty. The paper proposes that the mujāhadah approach be systematically integrated into rural family development programs, particularly to strengthen inner resilience, enhance biopsychosocial endurance, and empower the self-motivation of poor families to sustainably escape poverty.